Knowledge, attitude, and perception of the parents towards HPV vaccine administration to their children in Saudi Arabia - Dr Abrar Thabit; Dr. Saja Aljilani; Dr. Noura Alkinaidri; Mr. Abdulaziz Felimbam; Mr. Abubaker Bakhashab; Mr. Nawaf Bashah; Mr. Moheealdeen Habbal; Dr. Diena Almasri; Dr. Ragia Ghoneim (International Journal of Infectious Diseases)
Background: The prevalence of cancer due to human papillomavirus (HPV) infection is a major contributing factor to infection-related cancer cases globally. In Saudi Arabia, a recent initiative was launched to implement the HPV vaccination program, specifically for girls who age ≥12 years. This study aimed to assess the knowledge, attitude, and perception of parents in Saudi Arabia toward HPV vaccine. Methods: This was a survey-based study, where participants were interviewed in-person at pediatric clinics waiting areas and public places, such as malls. Eligible participants were parents of girls or boys aged 9-14 years. The survey was divided into five sections to gather data on sociodemographic traits, HPV vaccination knowledge, vaccine acceptance in general, knowledge of HPV, and acceptability of HPV vaccination. For knowledge questions, different viable answers were given different scores. Results: The preliminary phase included 118 participants that were interviewed in-person. Most of the participants were fathers (61%) with an age range of 30-39 years, were employed (69.5%), and held at least an undergraduate college degree (73.7%). Among the participants, only 55 (46.6%) expressed their willingness to vaccinate their children against HPV. Knowledge scores regarding HPV risk and its transmission were overall low. Younger age and high perception of benefits were correlated with willingness (rs= -0.26 and 0.40; P=0.023 and <0.001, respectively). Conversely, a proportion of the participants had a low perception of benefits (39.8%) and were afraid to vaccinate their children (29.7%). However, it was noted that among those who have heard of HPV in the past (38.1%) stated social media/internet as their major source of information (22%). Most of the participants expressed their interest in learning more about HPV from medical doctors than from other sources of information. Discussion: A study from Saudi Arabia assessed the willingness of female healthcare providers to receive HPV vaccine, where 45% expressed their willingness (AlSahmlan, et al. 2024). In that study, hesitancy was associated with lack of knowledge and older age. Such a proportion of willingness is similar to the proportion of parents willing to vaccinate their children. Additionally, poor knowledge regarding the vaccine and HPV infection seem to contribute to the vaccine hesitancy. Similar barriers to vaccination were also observed in another study of parents in the Eastern Region of Saudi Arabia (Alnaeem, et al. 2023). Conclusion: The initial phase of this study indicated lack of knowledge of the public in Saudi Arabia regarding HPV infection and its associated cancer risks, which may have been associated with the reduced willingness to vaccinate their children. Healthcare providers are encouraged to educate their patients and the public about HPV and the importance of the vaccine in media outlets and in their areas of practice.